Preparation method of passivator for sustainable corrosion prevention of chromium-free zinc-aluminum metal coating
By doping Zn-Al-LDHs nano containers in chromium-free passivator with non-chromium passivator, the Zn-Al-X-LDHs composite material is solved, and the chromium-free passivator is solved in a high temperature, high humidity and high salt environment. The problem of not being able to provide continuous passivation protection enables continuous passivation and efficient protection of the coating.
Patent Information
- Application Number
- CN202411492293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Existing chromium-free passivating agents cannot provide continuous passivation protection in high temperature, high humidity and high salt environments, resulting in an accelerated corrosion rate of zinc-aluminum powder and the coating loses its protective effect.
By using Zn-Al layered bimetallic hydroxides (Zn-Al-LDHs) as nano containers, non-chromium passivating agents such as phosphate and molybdate are doped into the intercalation layer to form Zn-Al-X- LDHs composite material. The material is exchanged responsively in the corrosive medium, and the stress releases the passivating agent to achieve continuous passivation.
The continuous passivation of the chrome-free coating metal powder and the substrate is achieved, and the protective performance of the coating in a high temperature, high humidity and high salt environment is improved, and the problem of the coating losing its protective effect is avoided.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an environmentally friendly functional metal coating, in particular to a method for preparing a passivating agent for sustainable corrosion protection of a chromium-free zinc-aluminum metal coating. Background Art
[0002] The passivation performance of non-chromium passivators in chromium-free Dacromet coatings, especially the continuous passivation performance, cannot be compared with chromates, and cannot provide continuous passivation protection for the zinc-aluminum powder and the substrate in the coating, which leads to a faster corrosion rate of the zinc-aluminum powder, and eventually the coating loses its sacrificial anode protection and the substrate corrodes. It is the lack of continuous passivation ability of non-chromium passivators that becomes the core key factor in the reduction of the corrosion resistance of the coating. Therefore, how to improve the continuous passivation ability of non-chromium passivators on metal powders and substrates is the key to the development of high-performance chromium-free Dacromet coatings, and it is also the bottleneck of the development of environmentally friendly alternative coatings.
[0003] Layered double hydroxides (LDHs) have been used as carriers of corrosion inhibitors in the field of corrosion protection of metal materials due to their excellent physical and chemical properties such as the adjustability of their structure and composition and anion exchange. LDHs can not only provide a physical barrier to the substrate, but also carry corrosion inhibitors or passivators through the intercalation structure to achieve the absorption and exchange of corrosive ions, providing intelligent and continuous protection for the substrate. Based on the original chromium-free Dacromet formula and coating design, Zn-Al layered double hydroxides (Zn-Al-LDHs) are used as nanocontainers to carry non-chromium passivators, and more non-chromium passivators such as molybdates and phosphates are doped into the Zn-Al-LDHs intercalation. By adjusting the type and content of the passivator, a new sheet-like continuous passivation component (i.e., Zn-Al-X-LDHs composite material, X is phosphate, molybdate, phosphomolybdate, etc.) is formed; this component will be laid flat in the chromium-free Dacromet coating in a consistent manner with the zinc-aluminum powder during film formation to obtain a "smart passivation" chromium-free Dacromet coating. When the corrosive medium, chloride ions, continue to invade, Zn-Al-X-LDHs will play a responsive exchange between the passivator and chloride ions in the intercalation layer, release passivators such as molybdate under stress, and achieve continuous passivation of the chromium-free coating metal powder and substrate, thereby improving the protective performance of the chromium-free Dacromet coating in the harsh corrosion environment of high temperature, high humidity and high salt.
[0004] Zn-Al-based LDHs composite materials have been widely used as carriers of corrosion inhibitors in the field of corrosion protection of metal materials such as organic coatings. The introduction of passivators into Zn-Al-LDHs achieves the responsive release of passivators and chloride ions, and has a long-lasting passivation effect. In addition, there is no conflict between the elements such as Zn and Al and the original formula composition of the chromium-free Dacromet coating, which greatly reduces the risk of coating stability. At the same time, LDHs has a lamellar structure similar to zinc and aluminum in chromium-free Dacromet. Therefore, Zn-Al-X-LDHs (X is phosphate, molybdate, phosphomolybdate, etc.) materials can achieve effective shielding and continuous passivation in chromium-free Dacromet coatings. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings. The method uses a zinc source and an aluminum source with a molar ratio of 3:1 to prepare a layered double metal hydroxide Zn-Al-LDHs, and uses one or more of phosphates, molybdates, borates, vanadates, rare earth metal salts, etc. as interlayer anions to synthesize a Zn-Al-X-LDHs intelligent passivating agent. When the addition amount is 0.5-3% and added to the zinc-aluminum coating, after curing at 240-360°C, the responsive exchange of the passivating agent and the chloride ion in the intercalation layer will be exerted, and the passivating agent such as molybdate will be released under stress, so as to achieve continuous passivation of the chromium-free coating metal powder and the substrate, and the anti-corrosion effect is excellent.
[0006] The technical solution of the present invention is: A method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, the method preparing Zn-Al-X-LDHs-x (wherein x is the mass percentage of Zn-Al-LDHs and the passivating agent); firstly preparing layered double hydroxide Zn-Al-LDHs, adding zinc source and aluminum source into deionized water, stirring magnetically for 0.5-3h to mix them evenly, then adding ammonium fluoride and urea and continuing stirring, transferring the obtained suspension to a high temperature reaction of a polytetrafluoroethylene liner The reaction mixture was reacted at 200-300 ° C for 24-48 hours, and then the precipitate was centrifuged, washed alternately with water and ethanol, and dried in a vacuum drying oven at 60-80 ° C for 4-8 hours to obtain Zn-Al-LDHs. After that, the passivator and Zn-Al-LDHs were added to ethanol in proportion, ultrasonically dispersed for 1-3 hours to form a uniform solution, continuously stirred for 10-12 hours, and finally dried in a vacuum drying oven at 60-80 ° C for 4-8 hours to obtain Zn-Al-X-LDHs-x.
[0007] The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, wherein the zinc source is one or more of zinc oxide, zinc chloride, zinc nitrate, and zinc sulfate, and the aluminum source is one or more of aluminum oxide, aluminum chloride, aluminum nitrate, and aluminum sulfate.
[0008] The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings comprises the following steps: the molar ratio of the aluminum source to the zinc source is 1:(2-4).
[0009] The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings comprises the following steps: the molar ratio of the aluminum source to ammonium fluoride is 1:(2-3), the molar ratio of the aluminum source to urea is 1:(5-7), and magnetic stirring is continued for 0.5-3h after addition.
[0010] The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings comprises the following steps: the centrifuge speed is 8000-10000 r / min, and the centrifugation time is 3-5 min.
[0011] In the method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, the rotation speed of the heat-collecting magnetic stirrer is 800-1300 r / min.
[0012] The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings is described, wherein the washing is completed when the pH value of the deionized water is 6-7.
[0013] The method for preparing a passivator for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, wherein the passivator X is one or more of phosphates, molybdates, borates, vanadates, and rare earth metal salts, preferably phosphomolybdic acid, sodium phosphomolybdate, sodium molybdate, and lanthanum nitrate, and is ground in advance and passed through a 100-mesh sieve for standby use.
[0014] The method for preparing a passivator for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, when the Zn-Al-X-LDHs is added in an amount of 0.5-3% to the zinc-aluminum coating, after being cured at 240-360°C, the passivator in the coating will be responsively exchanged with chloride ions, and the molybdate passivator will be released under stress, thereby achieving continuous passivation of the chromium-free coating metal powder and the substrate.
[0015] The advantages and beneficial effects of the present invention are: 1. Compared with chromate, the passivating agent Zn-Al-X-LDHs material provided by the present invention does not produce hexavalent chromium which is highly toxic and carcinogenic, and has the advantages of being green, environmentally friendly, pollution-free and harmless.
[0016] 2. Compared with other non-chromium passivators, the passivator Zn-Al-X-LDHs material provided by the present invention can exert the responsive exchange between the passivator and chloride ions in the intercalation layer, release passivators such as molybdate under stress, and realize the continuous passivation of chromium-free coated metal powder and substrate.
[0017] 3. The passivating agent Zn-Al-X-LDHs material provided by the present invention can prepare a chromium-free zinc-aluminum coating with good stability and storage properties without any other reaction influence.
[0018] 4. The passivating agent Zn-Al-X-LDHs material provided by the present invention can prepare a chromium-free zinc-aluminum coating that can be used for protection in harsh corrosive environments such as high temperature, high humidity, and high salt.
[0019] 5. The present invention is an intelligent passivating agent Zn-Al-X-LDHs material, which is added to the chromium-free zinc-aluminum coating, and can perform responsive exchange with chloride ions in a corrosive environment, realize the continuous release of non-chromium passivating agents such as molybdate, complete the continuous passivation function, and obtain a protective coating with optimal performance and environmental adaptability. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below by way of examples. Example 1
[0021] In this embodiment, the preparation method of the intelligent passivator applied to the zinc-aluminum coating is as follows: Step A was configured to prepare layered double hydroxide Zn-Al-LDHs. 2.68 g of zinc nitrate hexahydrate and 1.2 g of aluminum nitrate nonahydrate in a molar ratio of 3:1 were added to deionized water and magnetically stirred for 0.5 h to mix them evenly. Then, 0.3 g of ammonium fluoride and 1.2 g of urea were added and stirred continuously. The resulting suspension was transferred to a high-temperature reactor lined with polytetrafluoroethylene and reacted at 240°C for 24 h. The precipitate was then centrifuged, washed alternately with water and ethanol, and dried in a vacuum oven at 60°C to obtain Zn-Al-LDHs.
[0022] Configuration B step, preparation of Zn-Al-H3Mo 12 O 40 P-LDHs, 100 mg of phosphomolybdic acid and 50 mg of Zn-Al-LDHs were added to ethanol, ultrasonically dispersed for 2 h to form a uniform solution, stirred continuously for 12 h, and finally dried in a vacuum oven at 60 ° C to obtain Zn-Al-H3Mo 12 O 40 P-LDHs-50.
[0023] Prepared intelligent passivating agent Zn-Al-H3Mo 12 O 40After grinding, P-LDHs-50 was added to the zinc-aluminum coating at an addition amount of 0.5%. The thickness of the cured chromium-free zinc-aluminum coating was 9-12μm, with uniform thickness and smooth surface. Due to sustainable passivation, the salt spray resistance of the coating was greater than 1000h, and the corrosion resistance was far superior to the chromium-free zinc-aluminum coating with a single and unmodified phosphomolybdic acid as a passivator. The adhesion reached the 0-level standard measured by the hundred-grid scribing method, which is not much different from the metal surface adhesion level of existing common water-based coatings. Example 2
[0024] In this embodiment, the preparation method of the intelligent passivator applied to the zinc-aluminum coating is as follows: Step A was configured to prepare layered double hydroxide Zn-Al-LDHs. 2.68 g of zinc nitrate hexahydrate and 1.2 g of aluminum nitrate nonahydrate in a molar ratio of 3:1 were added to deionized water and magnetically stirred for 0.5 h to mix them evenly. Then, 0.3 g of ammonium fluoride and 1.2 g of urea were added and stirred continuously. The resulting suspension was transferred to a high-temperature reactor lined with polytetrafluoroethylene and reacted at 240°C for 24 h. The precipitate was then centrifuged, washed alternately with water and ethanol, and dried in a vacuum oven at 60°C to obtain Zn-Al-LDHs.
[0025] Configuration B step, preparation of Zn-Al-Na3Mo 12 O 40 P-LDHs, 100 mg of sodium phosphomolybdate and 50 mg of Zn-Al-LDHs were added to ethanol, ultrasonically dispersed for 1 h to form a uniform solution, stirred continuously for 12 h, and finally dried in a vacuum oven at 60 ° C to obtain Zn-Al-Na3Mo 12 O 40 P-LDHs-50.
[0026] Prepared intelligent passivation agent Zn-Al-Na3Mo 12 O 40 After grinding, P-LDHs-50 was added to the zinc-aluminum coating at an addition amount of 3%. The thickness of the cured chrome-free zinc-aluminum coating was 9-12μm, with uniform thickness and smooth surface. Due to sustainable passivation, the coating's salt spray resistance was greater than 1000h, and the corrosion resistance was far superior to the chrome-free zinc-aluminum coating with a single and unmodified sodium phosphomolybdate as a passivator. The adhesion was measured by the hundred-grid scribing method and reached the 0-level standard, which is not much different from the metal surface adhesion level of existing common water-based coatings. Example 3
[0027] In this embodiment, the preparation method of the intelligent passivator applied to the zinc-aluminum coating is as follows: Step A was configured to prepare layered double hydroxide Zn-Al-LDHs. 2.68 g of zinc nitrate hexahydrate and 1.2 g of aluminum nitrate nonahydrate in a molar ratio of 3:1 were added to deionized water and magnetically stirred for 0.5 h to mix them evenly. Then, 0.3 g of ammonium fluoride and 1.2 g of urea were added and stirred continuously. The resulting suspension was transferred to a high-temperature reactor lined with polytetrafluoroethylene and reacted at 240°C for 24 h. The precipitate was then centrifuged, washed alternately with water and ethanol, and dried in a vacuum oven at 60°C to obtain Zn-Al-LDHs.
[0028] In step B, Zn-Al-Na2MoO4-LDHs was prepared by adding 100 mg of sodium molybdate and 50 mg of Zn-Al-LDHs to ethanol, ultrasonically dispersing for 2 h to form a uniform solution, stirring continuously for 12 h, and finally drying in a vacuum drying oven at 60 °C to obtain Zn-Al-Na2MoO4-LDHs-50.
[0029] The prepared intelligent passivator Zn-Al-Na2MoO4-LDHs-50 was ground and added to the zinc-aluminum coating at an addition amount of 2%. The thickness of the cured chromium-free zinc-aluminum coating was 9-12μm, with uniform thickness and smooth surface. Due to sustainable passivation, the salt spray resistance of the coating was greater than 1000h, and the corrosion resistance was far superior to the chromium-free zinc-aluminum coating with a single and unmodified sodium molybdate as a passivator. The adhesion reached the 0-level standard measured by the hundred-grid scribing method, which is not much different from the metal surface adhesion level of existing common water-based coatings. Example 4
[0030] In this embodiment, the preparation method of the intelligent passivator applied to the zinc-aluminum coating is as follows: Step A was configured to prepare layered double hydroxide Zn-Al-LDHs. 2.68 g of zinc nitrate hexahydrate and 1.2 g of aluminum nitrate nonahydrate in a molar ratio of 3:1 were added to deionized water and magnetically stirred for 0.5 h to mix them evenly. Then, 0.3 g of ammonium fluoride and 1.2 g of urea were added and stirred continuously. The resulting suspension was transferred to a high-temperature reactor lined with polytetrafluoroethylene and reacted at 240°C for 24 h. The precipitate was then centrifuged, washed alternately with water and ethanol, and dried in a vacuum oven at 60°C to obtain Zn-Al-LDHs.
[0031] Step B was used to prepare Zn-Al-La(NO3)3-LDHs. 100 mg of lanthanum nitrate and 50 mg of Zn-Al-LDHs were added to ethanol, and ultrasonic dispersion was performed for 2.5 h to form a uniform solution. The solution was stirred continuously for 12 h, and finally dried in a vacuum drying oven at 60 °C to obtain Zn-Al-La(NO3)3-LDHs-50.
[0032] The prepared intelligent passivator Zn-Al-La(NO3)3-LDHs-50 was ground and added to the zinc-aluminum coating at an addition amount of 1.5%. The thickness of the cured chromium-free zinc-aluminum coating was 9-12μm, with uniform thickness and smooth surface. Due to sustainable passivation, the salt spray resistance of the coating was greater than 1000h, and the corrosion resistance was far superior to the chromium-free zinc-aluminum coating with a single and unmodified lanthanum nitrate as a passivator. The adhesion reached the 0-level standard measured by the hundred-grid scribing method, which is not much different from the metal surface adhesion level of existing common water-based coatings. Example 5
[0033] In this embodiment, the preparation method of the intelligent passivator applied to the zinc-aluminum coating is as follows: Step A was configured to prepare layered double hydroxide Zn-Al-LDHs. 2.68 g of zinc nitrate hexahydrate and 1.2 g of aluminum nitrate nonahydrate in a molar ratio of 3:1 were added to deionized water and magnetically stirred for 0.5 h to mix them evenly. Then, 0.3 g of ammonium fluoride and 1.2 g of urea were added and stirred continuously. The resulting suspension was transferred to a high-temperature reactor lined with polytetrafluoroethylene and reacted at 240°C for 24 h. The precipitate was then centrifuged, washed alternately with water and ethanol, and dried in a vacuum oven at 60°C to obtain Zn-Al-LDHs.
[0034] Configuration B step, preparation of Zn-Al-H3Mo 12 O 40 P-LDHs, 100 mg of phosphomolybdic acid and 75 mg of Zn-Al-LDHs were added to ethanol, ultrasonically dispersed for 3 h to form a uniform solution, stirred continuously for 12 h, and finally dried in a vacuum oven at 60 ° C to obtain Zn-Al-H3Mo 12 O 40 P-LDHs-75.
[0035] Prepared intelligent passivating agent Zn-Al-H3Mo 12 O 40 After grinding, P-LDHs-75 was added to the zinc-aluminum coating at an addition amount of 1%. The thickness of the cured chromium-free zinc-aluminum coating was 9-12μm, with uniform thickness and smooth surface. Due to sustainable passivation, the salt spray resistance of the coating was greater than 1000h, and the corrosion resistance was far superior to the chromium-free zinc-aluminum coating with a single and unmodified phosphomolybdic acid as a passivator. The adhesion reached the 0-level standard measured by the hundred-grid scribing method, which is not much different from the metal surface adhesion level of existing common water-based coatings.
Claims
1. A method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coatings, characterized in that: The method prepares Zn-Al-X-LDHs-x (wherein x is the mass percentage of Zn-Al-LDHs and a passivator); firstly, a layered double metal hydroxide Zn-Al-LDHs is prepared, a zinc source and an aluminum source are added to deionized water, magnetically stirred for 0.5-3 hours to make the mixture uniformly mixed, then ammonium fluoride and urea are added and stirred continuously, the obtained suspension is transferred to a high-temperature reactor lined with polytetrafluoroethylene, reacted at 200-300°C for 24-48 hours, then the precipitate is centrifuged, washed alternately with water and ethanol, and dried in a vacuum drying oven at 60-80°C for 4-8 hours to obtain Zn-Al-LDHs, then the passivator and Zn-Al-LDHs are added to ethanol in proportion, ultrasonically dispersed for 1-3 hours to form a uniform solution, stirred continuously for 10-12 hours, and finally dried in a vacuum drying oven at 60-80°C for 4-8 hours to obtain Zn-Al-X-LDHs-x.
2. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: The zinc source is one or more of zinc oxide, zinc chloride, zinc nitrate and zinc sulfate, and the aluminum source is one or more of aluminum oxide, aluminum chloride, aluminum nitrate and aluminum sulfate.
3. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 2, characterized in that: The molar ratio of the aluminum source to the zinc source is 1:(2-4).
4. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 3, characterized in that: The molar ratio of the aluminum source to ammonium fluoride is 1:(2-3), and the molar ratio of the aluminum source to urea is 1:(5-7). After addition, magnetic stirring is continued for 0.5-3h.
5. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: The centrifuge speed is 8000-10000 r / min, and the centrifugation time is 3-5 min.
6. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: The rotating speed of the heat collecting magnetic stirrer is 800-1300 r / min.
7. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: The washing is completed when the pH value of the deionized water is 6-7.
8. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: The passivating agent X is one or more of phosphate, molybdate, borate, vanadate, rare earth metal salt, preferably phosphomolybdic acid, sodium phosphomolybdate, sodium molybdate, lanthanum nitrate, and is ground in advance and passed through a 100-mesh sieve for later use.
9. The method for preparing a passivating agent for sustainable corrosion protection of chromium-free zinc-aluminum metal coating according to claim 1, characterized in that: When the Zn-Al-X-LDHs is added in an amount of 0.5-3% to the zinc-aluminum coating, after being cured at 240-360° C., the passivator in the coating will be responsively exchanged with chloride ions, and the molybdate passivator will be released under stress, thereby achieving continuous passivation of the chromium-free coating metal powder and the substrate.